Comparative study for different Demister Location in Multi Stage Flash (MSF) Flash Chamber (FC) - Mansour, Khamis (2013)
Multistage flash (MSF) is a widely used technology in large capacity salted water desalination plants. The enhancement in the thermal performance of this technology is still prospective and promising. In this research, vapor flow through the flash chamber (FC) was studied. Flow development in 2D simulation model of a real FC was investigated. Trajectory of liquid droplets was calculated using Lagrange approach. The continuity and Navier–Stokes equations for the continuous phase “vapor” were solved simultaneously with the particle equation using two equations k–ϵ turbulence model. The computational model was verified by comparing the predicated results (vapor pressure drop through the FC demister and moist separation efficiency) with those obtained from the published experimental data. The comparison showed a good agreement between both results with maximum deviation of less than −19.16%, however, most of the disagreement between both results is fewer than 10%. Four different demister locations were addressed. The first three locations are: on the right, left, and middle side of the FC inlet gate while the fourth one is the demister splitting on both sides of the FC. A comparison between the four different FCs in MSF plant was conducted on a basis of targeting higher separation efficiency with a reasonable vapor pressure drop across the demister. Two different velocity profiles for the flashing vapor entering the demister were adopted for four different types of the FCs. It was found that the third FC design (FC-III) has a better performance in terms of higher separation efficiency with relatively lower vapor pressure drop. The study could be considered as benchmark and helpful guidelines in a design of the FC shape in MSF desalination plants.